Localization of abdominal pain in uncomplicated appendicitis: Diagnostic value of McBurney and Lanz points in Kinshasa, Democratic Republic of the Congo - Kabanga, Thomas K.; Kapinga, Blaise M.; Kazadi, Deogratias B.; Kabanga, Herve K.; Kabanga, Alice T.; KILARA KAPENE, Tarcisse; Kabongo, Jeamarie M. (Orapuh Journal, 2025)
IntroductionAcute appendicitis is the leading cause of abdominal surgical emergencies, occurring most frequently among adolescents and young adults. Its diagnosis remains primarily clinical, based on the presence of localized pain with a positive McBurney’s sign.Purpose To assess the diagnostic value of McBurney and Lanz points in localising abdominal pain in patients with uncomplicated appendicitis, comparing their sensitivity, specificity, and concordance with the histologically confirmed diagnosis.Methods This descriptive cross-sectional study was conducted in two hospitals in Kinshasa: the Sino-Congolese Friendship Hospital and the Bon Berger Hospital Centre. It aimed to localise abdominal pain in uncomplicated appendicitis. Non-probability convenience sampling included 154 patients hospitalised between 1 January 2017 and 31 December 2020. Participants presented with abdominal pain suggestive of uncomplicated appendicitis, and diagnosis was confirmed through histological examination of the appendectomy specimen. Statistical analyses were performed using SPSS version 20.0, with a 95% confidence interval and a significance level of p < 0.05.Results Females constituted the majority of the study population (n = 120; 77.9%), with a sex ratio of 3.52. The 19–28 age group was the most represented (n = 68; 44.2%), with a 95% CI of 36.4%–52.0% and a non-significant p = 0.15. The mean age was 23.3 years. Pain in the right iliac fossa was the most common presentation (n = 148; 96.1%). Pain at McBurney’s point (PMBM) was observed in 138 patients (89.6%; 95% CI [84.7%, 94.5%]), followed by pain at the point midway between McBurney and Lanz (PMBL) in 128 patients (83.1%; 95% CI [77.0%, 89.2%]), and Lanz’s point in 107 patients (69.5%; 95% CI [61.9%, 77.1%]). p < 0.001 was considered highly significant.Conclusion Clinical examination remains essential in the diagnosis of appendicitis, with right iliac fossa pain as the principal symptom. Although McBurney’s and Lanz’s points are frequently used, they demonstrate limited sensitivity and specificity. The findings suggest that combining these anatomical landmarks with other clinical parameters may improve diagnostic accuracy and support more effective patient management.